Dietary leucine and fish oil cooperatively regulate skeletal myofiber type transformation via the CaMKII signaling pathway of pigs. Issue 1 (16th December 2022) - Gong, Saiming; Yin, Yunju; Han, Mengmeng; Guo, Liu; Duan, Yehui; Guo, Qiuping; Yin, Jie; Li, Fengna
Abstract : The mechanism of dietary leucine and fish oil on skeletal myofiber type transformations in pigs. Abstract : The study investigated the effects of dietary leucine (Leu) and fish oil (FO) on skeletal myofiber type transformations in pigs and their potential interactions. The results showed that Leu increased the content of Leu, upregulated myocyte enhancer factor-2C ( MEF2C ) and activated the CaMKII-AMPK/SIRT1-PGC-1α pathway in the longissimus dorsi (LD) muscle. FO increased adiponectin and fatty acid beta-oxidation of LD muscle. Activation of the adiponectin signaling pathway by FO further enhanced the CaMKII pathway and upregulated the expression of MEF2C . Moreover, we found that Leu increased cyclic AMP and caffeine, and FO increased linoleic acid and glutamine in muscle metabolites, which may be the cause of myofiber conversion. In conclusion, this study demonstrated that dietary Leu and FO co-regulated the transformation from glycolytic to oxidative skeletal myofiber type. It is hypothesized that there is an interaction between amino acids and polyunsaturated fatty acids, possibly via the CaMKII signaling pathway to upregulate MEF2 and mitochondrial biogenesis.